Effect of acute hyperglycaemia on gall bladder contraction induced by cholecystokinin in humans. Issue 8 (August 1993) - de Boer, S Y; Masclee, A A; Jebbink, M C; Schipper, J; Lemkes, H H; Jansen, J B; Lamers, C B
Abstract : This study examined the effect of acute hyperglycaemia, induced by intravenous glucose, on gall bladder motility. Six healthy volunteers were studied in random order on three occasions during normoglycaemia and hyperglycaemia with blood glucose concentrations stabilised at 8 and 15 mmol/l. Gall bladder volumes, measured with ultrasonography, were studied before and during infusion of stepwise increasing doses of cholecystokinin (CCK-33; 0.25, 0.5, and 1.0 IDU.kg-1.h-1). Each dose was given for 30 minutes. Pancreatic polypeptide (PP) secretion was determined as an indirect measure of cholinergic tone. Infusion of CCK-33 resulted in significant dose dependent reductions in gall bladder volume in all three experiments. Compared with normoglycaemia the gall bladder contraction was significantly (p < 0.05) reduced during infusion of 0.25 and 0.5 IDU kg-1.h-1 CCK-33 in the 8 mmol/l hyperglycaemic experiment, and during infusion of 0.25, 0.5, and 1.0 IDU kg-1.h-1 CCK-33 in the 15 mmol hyperglycaemic experiment. During hyperglycaemia basal plasma PP concentrations and PP secretion in response to CCK-33 were significantly (p < 0.05) reduced. It is concluded that blood glucose concentrations affect gall bladder motility, that an acute hyperglycaemia at 8 and 15 mmol/l reduces the gall bladder responsiveness to CCK-33 in a dose dependent manner, and that hyperglycaemia reduces basal and CCK-33 stimulated plasma PP concentrations, suggesting impaired cholinergic activity during hyperglycaemia.